Harmoni Arsitektur: Mengungkap Keindahan Fasad Masjid An-Nur Magelang Jawa Tengah - Muhamad Bima Satrio; Muhammad Ikhwal Afrizal (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The mosque facade is an important element in architectural art that influences visitors' perceptions and experiences. This study focuses on the An-Nur Mosque in Magelang, Central Java, which showcases the integration of traditional Javanese and Islamic architectural elements. The research method used is library research, collecting data from various literature sources, including books, journals, and relevant articles. The results show that the mosque's facade design combines the traditional Javanese joglo roof with domes and minarets, as well as elaborate carvings, creating a unique aesthetic. The use of local materials such as teak wood and andesite stone emphasizes local wisdom, while geometric ornaments and Arabic calligraphy enrich the spiritual meaning. Therefore, the An-Nur Mosque not only serves as a place of worship but also as a symbol of cultural and religious identity for the local community, creating harmony between local culture and Islamic values.